2020
DOI: 10.1088/1742-6596/1618/2/022016
|View full text |Cite
|
Sign up to set email alerts
|

Wind Farm Energy Production Optimization Via Wake Steering

Abstract: The wake steering technique consists in misaligning turbines with respect to the incoming wind with the goal of displacing their wake region and reducing the wake wind speed deficit, thus increasing the power production of other turbines downwind. In this paper, an algorithm is proposed to estimate the amount of production gain a wind farm could achieve by employing this technique. Details about data treatment are provided and an analytical wake model that can represent the wakes displacement is described. A m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Fortunately, and in contrast to AIC, many of the lessons learned with a column of turbines still apply in larger arrays. Both optimization techniques 3,36,102,103,111,114,119,120,128,137,140,145,148–150,157,158,161,163–165 and trial and error comparisons 108,123,164 of different arrangements of yaw misalignment angles have been tested and have arrived at different conclusions. Several studies have found that total power is optimized when the upstream turbines are misaligned the most and the misalignment angle is decreased as turbines are located farther downstream 3,108,123,146,164 .…”
Section: Wake Management Techniquesmentioning
confidence: 99%
See 3 more Smart Citations
“…Fortunately, and in contrast to AIC, many of the lessons learned with a column of turbines still apply in larger arrays. Both optimization techniques 3,36,102,103,111,114,119,120,128,137,140,145,148–150,157,158,161,163–165 and trial and error comparisons 108,123,164 of different arrangements of yaw misalignment angles have been tested and have arrived at different conclusions. Several studies have found that total power is optimized when the upstream turbines are misaligned the most and the misalignment angle is decreased as turbines are located farther downstream 3,108,123,146,164 .…”
Section: Wake Management Techniquesmentioning
confidence: 99%
“…Similarly, with wake steering the goal is to balance yawing frequently enough to maintain power maximization while avoiding overuse of the yawing components. One approach to implementing an optimization in a wind farm is to simulate all (or a subset of) the possible conditions and create a lookup table of optimal yaw angles 112,121,130,132,133,145,150 . Campagnolo et al 112 demonstrated the need for good models when generating these tables, and Howland et al 142 showed the strong dependence on atmospheric conditions.…”
Section: Wake Management Techniquesmentioning
confidence: 99%
See 2 more Smart Citations